Selective 6H-SiC White Light Emission by Picosecond Laser Direct Writing - Sicong Wang (Nature Portfolio, 2018)
Abstract Displaying a full or tuneable emission spectrum with highly efficient is significant for luminescent materials used in solid-state lighting. Silicon carbide (SiC) has potential for use in photoelectric devices that operate under extreme conditions. In this paper, we present a method to selectively modify the photoluminescence (PL) properties of SiC by ultrafast laser direct writing. Based on this method, visible white PL could be observed by the naked eye at room temperature under ultraviolet excitation. By increasing the laser power intensity from 40 to 80 MW/cm2, the PL of the irradiated samples increased and pure white sunlight-like emission with controlled colour temperature was realised. The optimised laser power intensity of 65 MW/cm2 achieved a desirable colour temperature similar to that of sunlight (x = 0.33, y = 0.33 and colour temperature of 5500 K) and suppressed blue emission. By direct laser irradiation along designed scanning path, a large-scale and arbitrary pattern white emission was fabricated. The origin of the white luminescence was a mixture of multiple luminescent transitions of oxygen-related centres that turned the Si-C system into silicon oxycarbide. This work sheds light on new luminescent materials and a preparation technique for next-generation lighting devices.